Identification of the types of preanalytical errors in a hematology laboratory: 1 year study at ESIC hospital, Chennai - Dr. V. Rajalakshmi; Dr. R. Muthu Krishnan; Dr. K. Rajeswari; Dr. A. Sathish Selvakumar (Tropical Journal of Pathology and Microbiology, 2017)
Objective: To evaluate the common causes of preanalytical errors in a fully automated hematology laboratory. Methods: Laboratory staff was instructed to record the rejected samples and the causes of such rejections of ward and outpatient samples collected in both wards and laboratory. Results: Of the 53344 samples received for hematological tests during the one year period from 1.1.2016 to 31.12.2016, 181 samples were rejected for analysis. This accounted for 0.3% of samples collected for hematological tests. The reasons for rejections with their incidences are as follows: Insufficient samples –35.3 %, Clotted sample –25.7 %, Wrong registration –15.0 %, Double registration –11.6 %, Inappropriate container –5.5 %, Sample spillage – 3.9 %. Conclusion: The overall percentage of rejection in our hematology laboratory is 0.3 % and insufficient sample is the most common cause for rejection. Adequate training, regular maintenance of a record of errors and periodic auditing will result in effective reduction of such errors and hence improvement in the overall performance of laboratory works.